Articular manifestations of Scheie's syndrome. Issue 4 (April 1992) - Hamilton, E; Pitt, P
Abstract : A patient with the clinical and biochemical features of Scheie's syndrome is reported. Radiological investigation has shown severe progressive juxta-articular cystic lesions, which have not, to our knowledge, previously been described in Scheie's syndrome.